2010
DOI: 10.1103/physrevc.81.054911
|View full text |Cite
|
Sign up to set email alerts
|

Model for hypernucleus production in heavy ion collisions

Abstract: We estimate the production cross sections of hypernuclei in projectile like fragment (PLF) in heavy ion collisions. The discussed scenario for the formation cross section of hypernucleus is: (a) Lambda particles are produced in the participant region but have a considerable rapidity spread and (b) Lambda with rapidity close to that of the PLF and total momentum (in the rest system of PLF) up to Fermi motion can then be trapped and produce hypernuclei. The process (a) is considered here within Heavy Ion Jet Int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…A reduction of the strange (s) quark mass from M s = 350 MeV to the current quark mass of approximately m s = 150 MeV gives a strangeness suppression factor γ 1 s ≈ 0.70. A similar value of γ 1 s (0.69) is obtained by increasing the string tension from κ 0 = 1.0 GeV fm −1 to κ = 3.0 GeV fm −1 [145]. However, if we consider that Schwinger tunneling could explain the thermal character of hadron spectra we can define an apparent temperature as a function of the average value of string tension ( κ ), T = √ 3 κ /4π [149].…”
Section: (Multi) Strangeness Production In Pb+pb Collisions At Lhc: H...supporting
confidence: 58%
See 2 more Smart Citations
“…A reduction of the strange (s) quark mass from M s = 350 MeV to the current quark mass of approximately m s = 150 MeV gives a strangeness suppression factor γ 1 s ≈ 0.70. A similar value of γ 1 s (0.69) is obtained by increasing the string tension from κ 0 = 1.0 GeV fm −1 to κ = 3.0 GeV fm −1 [145]. However, if we consider that Schwinger tunneling could explain the thermal character of hadron spectra we can define an apparent temperature as a function of the average value of string tension ( κ ), T = √ 3 κ /4π [149].…”
Section: (Multi) Strangeness Production In Pb+pb Collisions At Lhc: H...supporting
confidence: 58%
“…In previous publications [145], we studied the possible role of topological baryon junctions [25] and the effects of strong color field (SCF) in nucleus-nucleus collisions at RHIC energies. We have shown that the dynamics of the production process can deviate considerably from that based on Schwinger-like estimates for homogeneous and constant color fields.…”
Section: (Multi) Strangeness Production In Pb+pb Collisions At Lhc: H...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some are not accessible in experiments that produce hypernuclei off stable targets. However, the possibility of using heavy ion collisions to produce hypernuclei of widely varying mass and proton-neutron asymmetry is actively discussed [31,32] so that these hypernuclei may become accessible in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The second and presumably dominant mechanism for (anti)nuclei production is via final-state coalescence [7][8][9]. This production mechanism of light (anti)nuclei and (anti)hypernuclei is usually studied by the transport models plus the phase space coalescence model [10][11][12] and/or the statistical model [13][14][15][16], etc. In the thermodynamic model, the system is characterized by the chemical freeze-out temperature T ( ) ch and the kinetic freeze-out temperature T ( ) kin as well as the baryon and strangeness chemical potentials μ B and μ S .…”
Section: Introductionmentioning
confidence: 99%